1995 : the year the future began - Campbell, W. Joseph (University of California Press, 2015)
"A hinge moment in recent American history, 1995 was an exceptional year. Drawing on interviews, oral histories, memoirs, archival collections, and news reports, W. Joseph Campbell presents a vivid, detail-rich portrait of those memorable twelve months. This book offers fresh interpretations of the decisive moments of 1995, including the emergence of the Internet and the World Wide Web in mainstream American life; the bombing at Oklahoma City, the deadliest attack of domestic terrorism in U.S. history; the sensational 'Trial of the Century, ' at which O.J. Simpson faced charges of double murder; the U.S.-brokered negotiations at Dayton, Ohio, which ended the Bosnian War, Europe's most vicious conflict since the Nazi era; and the first encounters at the White House between Bill Clinton and Monica Lewinsky, a liaison that culminated in a stunning scandal and the spectacle of the president's impeachment and trial. As Campbell demonstrates in this absorbing chronicle, 1995 was a year of extraordinary events, a watershed at the turn of the millennium. The effects of that pivotal year reverberate still, marking the close of one century and the dawning of another"--Provided by publisher